Proteomic and Systematic Functional Profiling Unveils Citral Targeting Antibiotic Resistance, Antioxidant Defense, and Biofilm-Associated Two-Component Systems of Acinetobacter baumannii To Encumber Biofilm and Virulence Traits - Anthonymuthu Selvaraj (American Society for Microbiology, 2020)
ABSTRACT Acinetobacter baumannii has been reported as a multidrug-resistant bacterium due to biofilms and antimicrobial resistance mechanisms. Hence, novel therapeutic strategies are necessary to overcome A. baumannii infections. This study revealed that citral at 200 μg/ml attenuated A. baumannii biofilms by up to 90% without affecting viability. Furthermore, microscopic analyses and in vitro assays confirmed the antibiofilm efficacy of citral. The global effect of citral on A. baumannii was evaluated by proteomic, transcriptional, and in silico approaches. Two-dimensional (2D) gel electrophoresis and matrix-assisted laser desorption ionization–time of flight/time of flight (MALDI-TOF/TOF) analyses were used to assess the effect of citral on the A. baumannii cellular proteome. Quantitative real-time PCR (qPCR) analysis was done to validate the proteomic data and identify the differentially expressed A. baumannii genes. Protein-protein interactions, gene enrichment, and comparative gene network analyses were performed to explore the interactions and functional attributes of differentially expressed proteins of A. baumannii. Global omics-based analyses revealed that citral targeted various mechanisms such as biofilm formation, antibiotic resistance, antioxidant defense, iron acquisition, and type II and type IV secretion systems. The results of antioxidant analyses and antibiotic sensitivity, blood survival, lipase, and hemolysis assays validated the proteomic results. Cytotoxicity analysis showed a nontoxic effect of citral on peripheral blood mononuclear cells (PBMCs). Overall, the current study unveiled that citral has multitarget efficacy to inhibit the biofilm formation and virulence of A. baumannii. IMPORTANCE Acinetobacter baumannii is a nosocomial-infection-causing bacterium and also possesses multidrug resistance to a wide range of conventional antibiotics. The biofilm-forming ability of A. baumannii plays a major role in its resistance and persistence. There is an alarming need for novel treatment strategies to control A. baumannii biofilm-associated issues. The present study demonstrated the strong antibiofilm and antivirulence efficacy of citral against A. baumannii. In addition, proteomic analysis revealed the multitarget potential of citral against A. baumannii. Furthermore, citral treatment enhances the susceptibility of A. baumannii to the host innate immune system and reactive oxygen species (ROS). Cytotoxicity analysis revealed the nonfatal effect of citral on human PBMCs. Therefore, citral could be the safest therapeutic compound and can be taken for further clinical evaluation for the treatment of biofilm-associated infections by A. baumannii.